Comparison of Long‐Term Clinical Outcomes of Lesions Exhibiting Focal and Segmental Peri‐Stent Contrast Staining. Issue 3 (March 2016) - Tokuda, Takahiro; Yamawaki, Masahiro; Takahara, Mitsuyohi; Mori, Shinsuke; Makino, Kenji; Honda, Yosuke; Takafuji, Hiroya; Takama, Takuro; Tsutsumi, Masakazu; Sakamoto, Yasunari; Takimura, Hideyuki; Kobayashi, Norihiro; et al.
Abstract : Background: Peri‐stent contrast staining (PSS) after metallic drug‐eluting stent deployment is associated with target lesion revascularization and very late stent thrombosis. However, the type of PSS that influences the clinical outcomes is unknown. Therefore, we aimed to reveal which PSS type was influencing clinical outcomes. Methods and Results: This study included 5580 de novo lesions of 4405 patients who were implanted with a first‐ or second‐generation drug‐eluting stent and who were evaluated using follow‐up angiography within 12 months after stent implantation. We compared the clinical outcomes of patients divided into focal PSS and segmental PSS groups for 6 years after stent implantation. Total PSS was observed in 97 lesions (2.2%), of which 42 and 55 lesions were focal and segmental PSS, respectively. Baseline characteristics were similar between groups, except for intraoperative chronic total occlusion (segmental PSS=47.3% versus focal PSS=11.9%, P =0.0001). The incidence of segmental PSS tended to be higher in patients with a first‐generation drug‐eluting stent (83.6% versus 16.4%, P =0.05). The cumulative incidence of stent thrombosis in the 6 years of segmental PSS group was significantly higher than that of the focal PSS group (13.9% versus 0%, P =0.04). The cumulative incidence of overall target lesion revascularization for restenosis, excluding target lesion revascularization procedures for stent thrombosis, was significantly higher in the segmental PSS group (38.0% versus 0%, P =0.01). Conclusions: The incidence of segmental PSS tended to be higher in patients with a first‐generation drug‐eluting stent and appeared to be significantly associated with target lesion revascularization and stent thrombosis.